A good thing takes time: The role of preparation time in asynchronous video interviews - Johannes M. Basch; Falko Brenner; Klaus G. Melchers; Stefan Krumm; Luise Dräger; Helen Herzer; Evelyn Schuwerk (International Journal of Selection and Assessment, 2021)
Asynchronous video interviews (AVIs) are increasingly used to preselect applicants. Previous research found that interviewees in AVIs receive better interview ratings compared to other forms of interviews. It has been suggested that this difference could be due to the preparation time given for each AVI question. A pilot study confirmed that preparation time in AVIs is indeed beneficial for interview performance. Furthermore, our main study replicated the significant effect of preparation time on interview performance and revealed that it was mediated by active response preparation, whereas no mediation effects were found for strain and for the use of impression management. Finally, preparation time had no direct effect on fairness perceptions but a positive indirect effect via honest impression management.
Keywords: 650; applicant reactions; asynchronous video interviews; personnel selection; selection interviews; technology-mediated interviews